Micropropagation of red ginger (zingiber montanum koenig), a medicinal plant - Hamirah, M.N.; Hamsawi, Sani; Boyce, P.C; Sim, S.L. (APJMBB, 2010)
A protocol has been developed for the in vitro regeneration of red ginger (Zingiber montanum Koenig), a valuable medicinal plant. Rhizome buds of 1.5 to 2 cm long were surface sterilized with commercial bleach prior to culture on Gamborg B5 medium incorporated with Tetracycline at 15 ml/L and Plant Preservative Mixture at 2 ml/L. For induction of multiple shoots, three studies were conducted, (1) effects of different plant growth regulators, (2) effect sof whole and sectioned buds and (3) effects of culture phase. Thidiazuron (TDZ) at 0.5 mg/L was found to induce the highest shoot multiplication with a mean of 8.1 shoots per explant. Sectioned buds produced a mean of 4.6 shoots from each explant. As far the culture phase, liquid medium was found to be superior to solid medium. Rooting of propagules was conducted on B5 medium devoid of growth regulators. Acclimatization was conducted on medium containing a mixture of 1:1:1 soil, sand and peat with about 85% survivability.